2000
DOI: 10.1046/j.1570-7458.2000.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, biochemical, and behavioral uniformity among populations of Myzus nicotianae and Myzus persicae

Abstract: Prior to designation as distinct species, an appellation presently in question, the tobacco aphid, Myzus nicotianae Blackman (Homoptera: Aphididae), was classified as a tobacco‐feeding form of the green peach aphid, Myzus persicae (Sulzer). In this study, RAPD polymorphisms distinguished members of the Myzus persicae complex (M. persicae and M. nicotianae) from three outgroup Myzus species (M. cerasi (F.), M. hemerocallis Takahashi, and M. varians Davidson). Polymorphisms within the complex did not separate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
2
22
2
1
Order By: Relevance
“…Different patterns of performance have been found for M. persicae s.s. and M. persicae nicotianae , depending on the host plant (Clements et al., 2000). The specialist on tobacco shows a better performance on tobacco, although it may be reared on several species of five plant families under laboratory conditions (Semtner et al., 1998; Nikolakakis et al., 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different patterns of performance have been found for M. persicae s.s. and M. persicae nicotianae , depending on the host plant (Clements et al., 2000). The specialist on tobacco shows a better performance on tobacco, although it may be reared on several species of five plant families under laboratory conditions (Semtner et al., 1998; Nikolakakis et al., 2003).…”
Section: Methodsmentioning
confidence: 99%
“…A study of the host preference of both aphid taxa did not reveal differences between them, and host selection was described as a random process (Clements et al., 2000). In contrast, Nikolakakis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Subspecies status (as for Myzus persicae nicotianae Blackman) has been proposed for the tobacco‐feeding form of M. persicae (Margaritopoulos et al ., 2003; Eastop & Blackman, 2005) . Nevertheless, DNA studies on M. persicae , including some aimed specifically at comparing tobacco‐ and non‐tobacco‐feeding populations, have failed to find consistent diagnostic genetic markers (Margaritopoulos, Mamuris & Tsitsipis, 1998; Clements et al ., 2000a, b). DNA sequence data indicate that adaptation to tobacco must have occurred very recently, and that there is some introgression of genes from non‐tobacco‐feeding populations (Field et al ., 1994; Clements et al ., 2000b).…”
mentioning
confidence: 99%
“…However, laboratory experiments have demonstrated that M. p. nicotianae is able to survive and reproduce on species from at least five plant families, with a performance on sweet pepper, Capsicum annuum L. (Solanaceae), as good as on tobacco (Semtner et al, 1998;Basoalto et al, unpubl. data), and has been found on non-tobacco host plants in other countries (Clements et al, 2000). Additionally, all putative hosts of M. p. nicotianae (Semtner et al, 1998) can be colonized by M. persicae s.s., with the exception of N. tabacum, on which the latter cannot survive.…”
Section: Introductionmentioning
confidence: 73%